2021
DOI: 10.1111/abac.12214
|View full text |Cite
|
Sign up to set email alerts
|

Revealing Research Themes and Trends in 30 Top‐ranking Accounting Journals: A Text‐mining Approach

Abstract: This study reveals themes and trends in accounting research over the past 20 years by utilizing natural language processing and text‐mining techniques. We generated a corpus consisting of over 40,000 articles through multiple searches in EBSCOhost Business Source Premier, Scopus, and ScienceDirect to gather data from 30 highly ranked (A* and A) journals that were listed and categorized by the Australian Business Deans Council (ABDC) as the top accounting journals. Based upon predetermined inclusion and exclusi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 118 publications
0
6
0
1
Order By: Relevance
“…Consistent with prior reviews in the accounting discipline, we initially defined our review scope using the Australian Business Deans Council (ABDC) journal quality list and the Chartered Association of Business Schools’ Academic Journal Guide (AJG), which are commonly used as measures of journal quality and research performance (Alhossini et al, 2021; de Villiers & Hsiao, 2018; He et al, 2021; Kotb et al, 2020; Zengul et al, 2021). To mitigate criticisms associated with peer‐based journal rankings (Guthrie et al, 2019), we broadened our scope to include journals in the top two quartiles of the SCImago Journal Rank Indicator (SJR) metric.…”
Section: Methodsmentioning
confidence: 99%
“…Consistent with prior reviews in the accounting discipline, we initially defined our review scope using the Australian Business Deans Council (ABDC) journal quality list and the Chartered Association of Business Schools’ Academic Journal Guide (AJG), which are commonly used as measures of journal quality and research performance (Alhossini et al, 2021; de Villiers & Hsiao, 2018; He et al, 2021; Kotb et al, 2020; Zengul et al, 2021). To mitigate criticisms associated with peer‐based journal rankings (Guthrie et al, 2019), we broadened our scope to include journals in the top two quartiles of the SCImago Journal Rank Indicator (SJR) metric.…”
Section: Methodsmentioning
confidence: 99%
“…There is strong anecdotal evidence that poor corporate governance practices are associated with corporate failure, as was seen in the financial scandals of Enron, WorldCom and other high profile bankruptcies [21]. While corporate governance has been a rapidly growing area of the literature (Zengul et al ., 2021), there is comparatively little research that has investigated the relationship between corporate governance attributes (such as board composition and shareholder ownership/concentration) and corporate failure [22]. In an early study, Gilson (1990) reported that corporate default engenders significant changes in the ownership of firms' residual claims and in the allocation of rights to manage corporate resources.…”
Section: The Role Of Predictor Variablesmentioning
confidence: 99%
“…Over the decades, corporate social responsibility (CSR) has gained extensive attention from academics and practitioners (Zengul et al, 2021). CSR refers to firm activities that go beyond economic and legal requirements and serve social good in connection with stakeholders such as charitable donations (Deniz & Suarez, 2005; Marques et al, 2014; McWilliams & Siegel, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Finally, we add to the increasing literature on CSR (Zengul et al, 2021) by identifying the board chair as an important determinant. Several existing studies investigate how CEO characteristics determine CSR (Agle et al, 1999; Cronqvist & Yu, 2017; Deckop et al, 2006; Galaskiewicz, 1997; Petrenko et al, 2016; Waldman et al, 2006).…”
Section: Introductionmentioning
confidence: 99%